Self-assembly with degenerate prototropy - Baruah, Pranjal K.; Gonnade, Rajesh G.; Phalgune, U. D.; Sanjayan, G. J. (Journal of Organic Chemistry, 2005)
This work describes a rational approach for addressing the prototropy-related problems in heterocycle-based self-assembling systems by the use of degenerate prototropy. As a proof of principle, the utility of degenerate prototropy is demonstrated herein by developing heterocycle-based AADD-type self-assembling modules that exist as ``single set of protameric pair (duplex)'' in both solution and solid states. These self-assembling modules are quickly accessible in good yield by reacting 2-amino-5,5-disubstituted-1H-pyrimidine-4,6-diones, available in one step by the condensation of (x,a-dialkyl malonates and free guanidine, with isocyanates. Evidence from NMR spectroscopy, ESI mass spectrometry, and single-crystal X-ray diffraction studies confirmed the formation of molecular duplexes. The effect of electronic repulsion in duplex formation is also investigated. Their ready synthetic accessibility, remarkably high propensity to crystal formation, and the novel property of degenerate prototropy would make these novel self-assembling molecules promising candidates for many proposed applications.